FACTORS OF BASIC IMMUNIZATION COMPLETENESS IN 12-MONTH-OLD INFANTS IN BANDAR SETIA VILLAGE IN 2022 - Simamora, Lamtiar; Tarigan, Imarina; christine, christine dwi octhaviani; Butar Butar, Elestra Natalia; Putri, Grace Adelia (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Complete basic immunization in infants is an important indicator in improving child health and preventing diseases that can be prevented through immunization. Immunization plays an important role in reducing morbidity and mortality among infants. However, complete basic immunization coverage has not reached the expected target in several areas. This condition indicates that factors affecting immunization completeness still exist, including maternal knowledge about the importance, benefits, and schedule of immunization. Therefore, it is important to identify factors related to complete basic immunization. Objective: This study aims to analyze the relationship between maternal knowledge level and completeness of basic immunization in 12-month-old infants in Bandar Setia Village in 2022. Methods: This study used an analytical design with a cross-sectional approach. The population consisted of primipara mothers who had babies aged ≥10–36 months, with a total of 50 respondents. The sampling technique used was total sampling. Data were collected through questionnaires to measure maternal knowledge and immunization cards/KMS to assess infant immunization completeness. Data analysis was performed using univariate and bivariate analysis with the Chi-Square test at a 95% confidence level (α = 0.05). Results: The results showed that most respondents had sufficient knowledge, with 47 people (52.8%), followed by good knowledge with 33 people (37.1%), and poor knowledge with 9 people (10.1%). A total of 34.8% of infants had complete basic immunization, while 65.2% had incomplete immunization. The Chi-Square test showed a significant relationship between maternal knowledge level and immunization completeness (p = 0.009). Conclusion: Maternal knowledge is significantly related to complete basic immunization in infants. Improving knowledge through education and counseling can increase immunization coverage. Health workers are expected to provide information through posyandu activities, counseling, and educational media.